Perceptions of the impact of an advanced training programme on the management skills of health professionals in Gauteng South Africa - P Petrucka; J Mutyabule; F Senkubuge; D Cameron; V Pillay (South African Medical Association, 2017)
Background. South Africaâ€™s health sector spans the private and the public sectors. Within the sectors, health managers take on strategic leadership roles without formal training in management or leadership â€" a trend more common in the public sector than the private sector. Health managers are selected based on their clinical skills rather than their leadership or management skills.Objective. To compare self-rated competencies in management and leadership before and after training of the participants; to assess participantsâ€™ experience of the training programme; and to evaluate the management and leadership skills of the participants after training.Methods. A cross-sectional, descriptive analytical method and 360Â° interviewing were used in this study. Participants were evaluated ~18 months after completion of the training programme. A 360Â° evaluation (360Â° E) of six of the 12 leadership/management competencies was done with the supervisors, colleagues, and subordinates of the participants.Results. All participants rated themselves as improved in 12 managerial and leadership competencies. The 360Â° E affirmed five of these competenciesÂ  as improved, with the ability to create and implement a marketing plan rating poorly.Conclusion. Training in management leads to improvement in both leadership and managerial skills of health professionals.